The determinants of foreign direct investment: what is the evidence for Africa? - Moreira, Sandrina Berthault (2013)
The main purpose of the present paper is to provide an overall analysis of recent studies that both focus on Africa and examine the various factors that attract or deter Foreign Direct Investment (FDI) in Africa, in order to find answers to the following question: What are the determinants / impediments of FDI to Africa? To that end I have based my research on the articles published in all the economic journals found in the Econlit database from January 1969 up to May 2007. The keywords “foreign direct investment” and “Africa” yielded ten papers on FDI Determinants to Africa, which are the object of the present paper.